A new species of lizard Placosoma Tschudi, 1847 (Squamata: Gymnophthalmidae) from the relictual forest mountains of the State of Ceará, Brazil - Borges-Nojosa, Diva Maria; Caramaschi, Ulisses; Rodrigues, Miguel Trefaut (Zootaxa, 2016)
A new species of Placosoma Tschudi, 1847, until now restricted to the Atlantic Forest areas of southeastern Brazil is described based on specimens obtained about 1700 km north to the current distribution of the genus. Placosoma limaverdorum spec. nov. is apparently endemic to three “brejos-de-altitude”, relictual forest mountains surrounded by dry Caatingas, in the State of Ceará, northeastern Brazil. It differs from their congeners by the presence of an undivided transparent palpebral disk, a divided nasal scale with a central nostril, a deep tympanic recess, a distinctive and thin light vertebral stripe on the dorsal surface of the head, body and tail, femoral pores present only in males (21–26), preanal pores absent and additionally by having 21–24 rows of transverse ventral scales, 34–38 dorsals, dorsal, lateral and ventral scales smooth, dorsal scales quadrangular, longer than wide, except in the neck region, where they are wider than long.